Symptomatic and asymptomatic enteric protozoan parasitic infection and their association with subsequent growth parameters in under five children in South Asia and sub-Saharan Africa. - Rina Das; Parag Palit; Md Ahshanul Haque; Myron M Levine; Karen L Kotloff; Dilruba Nasrin; M Jahangir Hossain; Dipika Sur; Tahmeed Ahmed; Robert F Breiman; Matthew C Freeman; A S G Faruque (PLoS Neglected Tropical Diseases)
Background Entamoeba histolytica, Giardia, and Cryptosporidium are common intestinal protozoan parasites that contribute to a high burden of childhood morbidity and mortality. Our study quantified the association between intestinal protozoan parasites and child anthropometric outcomes among children under-5. Methods We analyzed data from 7,800 children enrolled in the Global Enteric Multicenter Study (GEMS) across seven study sites that were positive for intestinal protozoan parasites between December 2007 and March 2011. Parasites were assessed using stool immunoassays (ELISA). We applied multiple linear regression to test the association between any or concurrent parasite and child anthropometric outcomes: length/height-for-age (HAZ), weight-for-age (WAZ), and weight-for-length/height (WHZ) z-score after 60 days of enrollment. Models were stratified by diarrheal symptoms, driven by the study design, and adjusted for potential covariates. Findings During the follow-up at day 60 after enrollment, child anthropometric outcomes, among the asymptomatic children showed, negative associations between Giardia with HAZ [β: -0.13; 95% CI: -0.17, -0.09; p<0.001] and WAZ [β -0.07; 95% CI: -0.11, -0.04; p<0.001], but not WHZ [β: -0.02; 95% CI:-0.06, 0.02; p = 0.36]; Cryptosporidium with WAZ [β: -0.15; 95% CI: -0.22, -0.09; p<0.001] and WHZ [β: -0.18; 95%CI: -0.25, -0.12; p<0.001], but not with HAZ [β: -0.03; 95% CI: -0.09, 0.04; p = 0.40]. For symptomatic children, no associations were found between Giardia and anthropometry; negative associations were found between Cryptosporidium with HAZ [β: -0.17; 95% CI: -0.23, -0.11; p<0.001], WAZ [β: -0.25; 95% CI: -0.31, -0.19; p<0.001] and WHZ [β: -0.23; 95% CI: -0.30, -0.17; p<0.001]. Among the asymptomatic 24-59 months children, Giardia had a negative association with HAZ [β: -0.09; 95% CI: -0.15, -0.04; p = 0.001]. No significant associations were found between E. histolytica with child growth. Conclusions While some studies have found that Giardia is not associated with (or protective against) acute diarrhea, our findings suggest that it is associated with growth shortfall. This observation underscores the need for preventive strategies targeting enteric protozoan parasites among young children, to reduce the burden of childhood malnutrition.